A GAUSSIAN MIXTURE MODEL-BASED SPEAKER RECOGNITION SYSTEM - Gorai, Kumari Piu; Abraham, Thomas (Asian Journal of Pharmaceutical and Clinical Research, 2017)
A human being has lot of unique features and one of them is voice. Speaker recognition is the use of a system to distinguish and identify a person from his/ her vocal sound. A speaker recognition system (SRS) can be used as one of the authentication technique, in addition to the conventional authentication methods. This paper represents the overview of voice signal characteristics and speaker recognition techniques. It also discusses the advantages and problem of current SRS. The only biometric system that allows users to authenticate remotely is voice-based SRS, we are in the need of a robust SRS.